Physiological and Gene Expression Responses of Crassostrea ariakensis to Salinity Stress - Miaomiao YANG; Sudong XIA; Zhihong LIU; Xiujun SUN; Liqing ZHOU; Peizhen MA; Zhuanzhuan LI; Biao WU (Progress in Fishery Sciences, 2025)
Oysters are keystone species in marine ecosystems and essential for restoring ecological function and maintaining biodiversity maintenance. However, global climate change and increasing human activities have intensified environmental fluctuations in marine habitats, which greatly affect the growth and physiological functions of oysters and other marine organisms. Organisms in these environments have developed adaptive regulatory mechanisms. Crassostrea ariakensis is an economically important bivalve that inhabits estuarine areas along the coast of China and crucial for delivering essential ecological services. However, a lack of research exists on the physiological responses of C. ariakensis to frequent and substantial salinity variations in these estuaries.In this study, we investigated the physiological responses and key gene alterations in C. ariakensis under salinity stress by analyzing changes in respiration, ammonia excretion, ingestion, and clearance rates under various salinity conditions. The findings provide valuable data and insights for a comprehensive understanding of the physiological and metabolic responses of oysters to salinity stress. This study had different salinity gradients (5, 15, 25, 35, and 45), whereas a salinity of 25 served as the control group. Seawater, freshwater, and seawater crystals were used to establish environments with different salinities, and oyster individuals were randomly assigned to different salinity groups, with three individuals per group. Following 4 h of salinity stress treatment, the gills, adductor muscle, mantle tissue, and labial palps of the oysters were individually removed and promptly frozen in liquid nitrogen at −80 ℃ for subsequent analysis. The respiration, ammonia excretion, ingestion, and clearance rates of the oysters were measured using the static water method. Based on the β-actin gene as a reference, the expressions of the CarHsp70, CarHyou1, and CarDANJC2 genes were detected using RT-qPCR. The reaction system (10 μL) comprised the following: 0.2 μL each of upstream and downstream primers, 1 μL of template cDNA, 5 μL of 2× ChamQ SYBR Color qPCR Master Mix, and 3.6 μL of diethyl pyrocarbonate water. The reaction conditions were as follows: pre-denaturation at 95 ℃ for 10 min, denaturation at 95 ℃ for 10 s, and annealing at 60 ℃ for 30 s, for 40 cycles. Each group included six biological replicates, with each biological replicate conducted in triplicate. The results demonstrated that within a salinity range of 5–45, the respiration and ammonia excretion rates of C. ariakensis initially increased and subsequently decreased, with peak values observed at a salinity of 35. Similarly, the ingestion and clearance rates of C. ariakensis exhibited an initial increase, followed by a decrease within the same salinity range, with the maximum clearance rate observed at a salinity of 15 and the minimum value observed at a salinity of 45. In addition, the research revealed substantial effects of salinity stress on gene expression, particularly for CarHsp70. The RT-qPCR results showed that the three genes (CarHsp70, CarHyou1, and CarDANJC2) were expressed in the gills, mantle tissue, adductor muscle, and lip tissue of C. ariakensis, with the highest expression level observed in the adductor muscle. Changes in salinity significantly affected the expression of the three genes in the HSP family of C. ariakensis. Following salinity stress, the expression levels of the three genes in gill tissues exhibited an upward trend. Upon a 10-unit rise in salinity, the expression levels of CarHsp70, CarHyou1, and CarDANJC2 were upregulated by 4.36-, 3.58-, and 2.08-fold, respectively, compared to the control group. Conversely, a 10-unit drop in salinity resulted in adjustments to 3.62-, 2.97-, and 2.05-fold, respectively. Upon a 20-unit rise in salinity, the expression levels of the three genes were 7.13-, 4.68-, and 2.72- higher than those of the control group, respectively. Conversely, with a 20-unit drop in salinity, the expression levels were 5.92-, 6.04-, and 2.54- higher than those of the control group, respectively.This study elucidates the physiological and molecular responses of C. ariakensis to different salinity conditions, including respiration, ammonia excretion, ingestion, and clearance rates, and the expression changes of HSP family genes in response to salinity stress. Within a defined salinity range, the respiratory metabolic activities of shellfish progressively increased with rising salinity; however, beyond a specific threshold, these activities were inhibited. The three genes (CarHsp70, CarHyou1, and CarDANJC2) are essential for physiological functions in different shellfish tissues and may exhibit synergistic effects in response to environmental stress. Their expression patterns provide insights into the mechanisms underlying the adaptation of organisms to environmental changes. This research enhances our scientific understanding of the adaptability of C. ariakensis to salinity variations and offers substantial guidance for the sustainable development of the oyster farming industry and genetic improvement. Additionally, it provides reference material for further investigations into the adaptability of oysters to salinity changes.